2021
DOI: 10.1021/acs.energyfuels.1c00925
|View full text |Cite
|
Sign up to set email alerts
|

Improved Gas Permeation Properties of 6FDA-TrMPD Mixed-Matrix Membrane with SAPO-34 Crystals Toward CO2 Separation

Abstract: Herein, an improved mixed-matrix membrane (MMMs) was fabricated through a facile solution-casting process of simply incorporating SAPO-34 zeolites as the inorganic material into 6FDA-TrMPD (PI) polymer. The morphology, crystallinity, and thermal stability of the MMMs were investigated by SEM, XRD, and DSC, respectively. The effect of zeolite loading on the gas permeations of the resultant MMMs was studied. The permeability values of the as-prepared MMMs for CO2, N2, and CH4 were enhanced. For the CO2/CH4 and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…For polymers in particular, the molecular design occurs either at the monomer level prior to the polymerization process or through postpolymerization modification of the polymer’s backbone. , Both methods have demonstrated to improve certain targeted properties of the final products. Other strategies to control material properties consist of mixing polymeric materials with inorganic additives to incorporate new features into membranes matrices, such as metal–organic frameworks (MOFs), , covalent organic frameworks (COFs), , nanoparticles, zeolites, ,, and others, to produce the so-called mixed matrix membranes (MMMs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For polymers in particular, the molecular design occurs either at the monomer level prior to the polymerization process or through postpolymerization modification of the polymer’s backbone. , Both methods have demonstrated to improve certain targeted properties of the final products. Other strategies to control material properties consist of mixing polymeric materials with inorganic additives to incorporate new features into membranes matrices, such as metal–organic frameworks (MOFs), , covalent organic frameworks (COFs), , nanoparticles, zeolites, ,, and others, to produce the so-called mixed matrix membranes (MMMs).…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Both methods have demonstrated to improve certain targeted properties of the final products. Other strategies to control material properties consist of mixing polymeric materials with inorganic additives to incorporate new features into membranes matrices, such as metal−organic frameworks (MOFs), 16,17 covalent organic frameworks (COFs), 18,19 nanoparticles, 20 zeolites, 3,6,21 and others, to produce the so-called mixed matrix membranes (MMMs).…”
Section: ■ Introductionmentioning
confidence: 99%
“…87 Jiang et al 88 introduced a zeolite thin layer into a PSF/Matrimid hollow fiber membrane and found that the selectivity for CO 2 in a CO 2 /CH 4 mixed system was enhanced by 50%. Analogously, Wu et al 89 prepared an improved mixed-matrix membrane (MMMs) by incorporating SAPO-34 zeolites as an inorganic material in the 6FDA–TrMPD (PI) polymer, and the CO 2 permeability of the 40 wt% SAPO-34 crystal-loaded MMMs increased from 751 to 1663 barrer, which corresponded to an increase of 121% compared with the neat 6FDA–TrMPD membrane ( Fig. 4 ).…”
Section: Membranes For Carbon Dioxide Separationmentioning
confidence: 85%
“…This increased the free volume of the polymer and enhanced its gas permeation properties. 89 The above-mentioned inorganic-organic composite membranes had obvious advantages in CO 2 selective separation; however, there are still some issues to be addressed. The interaction mechanism between the polymer and inorganic ller interface is not clear, inorganic llers are difficult to disperse in the polymer matrix, they lack the foundation for large-scale manufacturing and application, and the CO 2 gas separation membranes still have a lot of room for improvement.…”
Section: Composite Membranesmentioning
confidence: 99%